Minimisation of Microbial Reservoirs and Infection Risks From Washbasin U-bend Traps Using a Novel Automated Disinfection System with Electrochemically Activated Solutions - SWAN, JAMES STEPHEN (Trinity College Dublin. School of Dental Sciences. Discipline of Dental Science, 2017)
Background: Washbasin and sink U-bends are ubiquitous in virtually all buildings including hospitals and smaller healthcare premises. They have been used for over a century and their principal purpose is to prevent foul odours emanating from wastewater pipes from entering buildings. U-bends are designed to retain a small volume of water, which acts as the seal preventing the passage of sewer gas from wastewater pipework. The water retained in U-bends is frequently stagnant, which encourages the growth and proliferation of microbial biofilms, populated predominantly by Gram-negative bacterial species and especially by Pseudomonas aeruginosa. Over the past two decades there have been numerous reports of nosocomial outbreaks of infection related directly or indirectly to contaminated U-bends. Three different approaches at addressing this problem have been used previously including the application of chemical disinfectants such as bleach, the replacement of sanitary fixtures and/or U-bends and the use of a U-bend heating element together with vibrational cleaning. The first two approaches worked well in several studies reducing contamination and infection risks in the short term, but failed to provide a long-term solution due to recolonisation of U-bends and the associated pipework with biofilm. The use of U-bend heating elements together with vibrational cleaning was shown to be effective, but the approach is expensive as the heating elements are in constant operation. Electrochemically activated (ECA) solution generators produce two solutions through activation of dilute brine. These include a metastable oxidant solution termed ?anolyte? (predominantly hypochlorous acid (HOCl)) and a second solution termed ?catholyte? with detergent properties (predominantly sodium hydroxide (NaOH)) The solutions are generated by passing a brine solution through a flow-through electrolytic cell. Anolyte is highly microbiocidal and capable of penetrating biofilms. Previous studies from this laboratory have shown that treatment of water supplied to dental units and washbasins with residual anolyte consistently eliminates biofilm and provides output water virtually free of contamination. Aim: The purpose of this study was to investigate whether periodic treatment of washbasin U-bends and associated pipework with catholyte solution as a cleaning agent followed by anolyte solution as a disinfectant could minimise biofilm contamination of U-bends. Achieving this objective would require developing an approach to seal the wastewater outflow pipework from washbasins so that U-bends and associated pipework could be completely filled with ECA solutions for specified periods of time for maximum efficacy. A second objective was to automate U-bend decontamination with ECA solutions. Methods: Initially three identical washbasin U-bends were manually filled with catholyte solution followed by anolyte solution for five min each once weekly for five weeks. Three additional identical washbasin U-bends were used as controls. A programmable system was then developed with one washbasin that automated this process using an actuator-controlled ball valve to seal the wastewater outlet pipe and chemical-resistant dosing pumps to dose ECA solutions into the U-bend and associated pipework. A Programmable Logic Controller was used to coordinate the sequence of operation of the actuator and dosing pumps. This U-bend had three cycles of five min catholyte followed by five min anolyte treatment a week for three months. Quantitative bacterial counts from treated and control U-bends were determined following each round of ECA treatment on blood agar (CBA), R2A, PAS and PA agars following automated treatment and on CBA and R2A following manual treatment. Bacterial identification was determined by comparing small ribosomal subunit rRNA gene sequences with consensus sequences for individual bacterial species in the EMBL/GenBank databases. Results: The average bacterial density from untreated U-bends throughout the study was >1 x 105 CFU/swab on all media with Pseudomonas aeruginosa accounting for approximately 50% of bacterial counts. Manual treatment of U-bends with ECAs reduced counts significantly (<100 CFU/swab) (P <0.01 for CBA; P <0.005 for R2A). Pseudomonas aeruginosa was eliminated from the U-bend subjected to automated ECA-treatment, with average bacterial counts over 35 cycles on CBA, R2A, PAS and PA of 2.1(?4.5) (P<0.0001), 13.1(?30.1) (P<0.05), 0.7(2.8) (P<0.001) and 0(?0) (P<0.05) CFU/swab, respectively. Following the three-month study period, the ECA-treated and control U-bends were removed and cut in cross-section and segments examined by electron microscopy, which revealed the virtual elimination of biofilm from the ECA-treated U-bend. In contrast, the control U-bend was heavily fouled with dense pigmented biofilm. Conclusion: Microbial contamination of washbasin U-bends can be consistently minimised by automated decontamination with ECA solutions. Future Developments: Work is in progress to develop a large-scale system for simultaneous automated decontamination of multiple washbasin U-bends.
APPROVED
Keywords: U-bends; Microbial biofilm; Hand washbasins; Electrochemically activated solutions; decontamination; anolyte; catholyte; automated decontamination; Pseudomonas aeruginosa; Wastewater; Gram-negative bacteria; Hospital acquired infections